2022
DOI: 10.1007/s12149-022-01769-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated semi-quantitative amyloid PET analysis technique without MR images for Alzheimer’s disease

Abstract: Objective Although beta-amyloid (Aβ) positron emission tomography (PET) images are interpreted visually as positive or negative, approximately 10% are judged as equivocal in Alzheimer’s disease. Therefore, we aimed to develop an automated semi-quantitative analysis technique using 18F-flutemetamol PET images without anatomical images. Methods Overall, 136 cases of patients administered 18F-flutemetamol were enrolled. Of 136 cases, five PET images each with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In contrast, several studies (Bourgeat et al, 2018;Edison et al, 2013;Fujishima & Matsuda, 2022;Imabayashi et al, 2022;Saint-Aubert et al, 2014;Tsubaki et al, 2020), including our own research (Fujishima & Matsuda, 2022), have reported anatomic standardization using the amyloid PET template alone without MRI. Out of these studies, the uses of an adaptive template generated from a linear combination of an amyloid-negative and amyloid-positive template with a weight-optimized algorithm have obtained comparable CL scales to those obtained with the standard MRI-guided method (Bourgeat et al, 2018;Fujishima & Matsuda, 2022;Imabayashi et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, several studies (Bourgeat et al, 2018;Edison et al, 2013;Fujishima & Matsuda, 2022;Imabayashi et al, 2022;Saint-Aubert et al, 2014;Tsubaki et al, 2020), including our own research (Fujishima & Matsuda, 2022), have reported anatomic standardization using the amyloid PET template alone without MRI. Out of these studies, the uses of an adaptive template generated from a linear combination of an amyloid-negative and amyloid-positive template with a weight-optimized algorithm have obtained comparable CL scales to those obtained with the standard MRI-guided method (Bourgeat et al, 2018;Fujishima & Matsuda, 2022;Imabayashi et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, several studies (Bourgeat et al, 2018;Edison et al, 2013;Fujishima & Matsuda, 2022;Imabayashi et al, 2022;Saint-Aubert et al, 2014;Tsubaki et al, 2020), including our own research (Fujishima & Matsuda, 2022), have reported anatomic standardization using the amyloid PET template alone without MRI. Out of these studies, the uses of an adaptive template generated from a linear combination of an amyloid-negative and amyloid-positive template with a weight-optimized algorithm have obtained comparable CL scales to those obtained with the standard MRI-guided method (Bourgeat et al, 2018;Fujishima & Matsuda, 2022;Imabayashi et al, 2022). However, our correlation analysis (Fujishima & Matsuda, 2022) between this PET-alone method and the standard MRIguided method showed that the CL scales slightly deviated from the validation criteria for 18 F-florbetapir from the Alzheimer's Disease Neuroimaging Initiative dataset (slope, 1.028; intercept, −4.302; R 2 , .974).…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, conventional morphological standardization based on normal typical examples, as done in FDG-PET or CBF SPECT, may lead to increased errors in individual subjects [17][18][19]. To address this issue, an approach called the adaptive atlas method has been reported, which assumes that amyloid PET images in actual subjects can be linearly approximated from typical amyloid-positive and -negative images [8][9][10][11][12]. This method uses a weighted average image of typical positive and negative images as the template image for morphological standardization.…”
Section: Adaptive Template Registration Methodsmentioning
confidence: 99%
“…However, in amyloid PET, an Adaptive Template Registration (ATR) method has been proposed as a solution, where templates for amyloid-positive and -negative subjects are prepared for analysis of 18F-utemetamol PET image data. Several weighted images are created from these templates, and the most appropriate weighted image is selected as the template for standardizing PET images, with successful outcomes [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to CapAIBL, two other softwares have been developed to calculate the CL values. First, VIZCalc is a novel automated semiquantitative analysis technique without MRI that is primarily used for processing 18F-flutemetamol PET images [ 10 ]. Its core feature lies in the weighted average image of the positive and negative template methods, which obtains the optimal template and resolves the issue of overestimation of SUVR values encountered in traditional average template-based standardization.…”
Section: Introductionmentioning
confidence: 99%